The Effect of Regulatory Harmonization on Cross-border Labor Migration: Evidence from the Accounting Profession - Ulf Brüggemann; Matthew J. Bloomfield; Hans B. Christensen; Christian Leuz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The paper examines the effect of international regulatory harmonization on cross-border labor migration. We analyze directives in the European Union (EU) that harmonized accounting and auditing standards. This regulatory harmonization should make it less costly for those who work in the accounting profession to move across countries. Our research design compares the cross-border migration of accounting professionals relative to tightly-matched other professionals before and after regulatory harmonization. We find that, on average, labor migration in the accounting profession increases relative to comparable professions by roughly 15% after harmonization. The findings illustrate that diversity in rules constitutes an important economic barrier to cross-border labor mobility and, more specifically, that accounting harmonization can have a meaningful effect on cross-border migration.
Keywords: J44; J61; K22; 330